Yielding Phenomena of Aortic Wall and Intramural Collagen Fiber Alignment: Possible Link to Rupture Mechanism of Aortic Aneurysms - Shukei SUGITA; Takeo MATSUMOTO (Journal of Biomechanical Science and Engineering, 2013)
Estimation of wall strength of the aortic aneurysms is necessary for the prediction of their rupture risk. We previously found a significant correlation between their tensile strength σMAX and a yielding parameter τσ, which is the stress when tangent elastic modulus reaches at 63% of the plateau level. This may indicate that the wall strength is estimated from their pressure-diameter relationship. Here we show a possible mechanism of the correlation between τσ and σMAX by focusing on alignment of collagen fibers. Thin (150-µm) slices of porcine thoracic aortas were uniaxially stretched in circumferential direction until failure under a microscope, and a retardance, a phase shift when polarized light passes through a birefringent material, was measured as the degree of collagen fiber alignment. Strength σMAX correlated significantly with τσ as obtained previously. The retardance increased with the increase in the stress and reached a plateau at the stress σRet-plateau, indicating that σRet-plateau is the stress at which most of the intramural collagen fibers have aligned. The stress σRet-plateau correlated significantly with τσ and both parameters has similar values. This may indicate that the aortic wall yields when all of collagen fibers become straight. Smaller σRet-plateau means that most collagen fibers are stretched and loaded at smaller stress, resulting in failure at smaller stress. This seems to be a reason for the significant correlation between τσ and σMAX.